Hydrogen production by steam gasification of Hungarian brown coal char - Mai, Thuan Duc; Kállay, András Arnold (Multidiszciplinaris Tudomanyok, 2022)
Presently, the hydrogen is mainly generated from fossil fuels (natural gas and coal). The thermochemical conversion processes of carbon-based materials to hydrogen-rich gas has been widely described in the literatures. In which, the steam gasification is highly recommended for this purpose. The experimental steam gasification of Hungarian brown coal char was conducted in a single stage fixed-bed reactor with 80 mm of inner diameter and 1,200 mm of effective length. The experiments were carried out at 700, 800 and 900 °C of gasification temperature within 5 g/min of steam flow rate and 5, 7.5 and 10 g/min of steam flow rate within 900 °C of gasification temperature. The aim of this study is to determine the performance of Hungarian brown coal char during the gasification with the variation of gasification temperature and steam flow rate, as well as the hydrogen production during the gasification process. The gasification temperature plays an important role in the conversion process in the gasifier, as well as the change in the synthesis gas composition. The introduction of higher steam flow rate can also improve the reduction process. The highest total hydrogen yield of 1.8 Nm3 was gained at 900 °C of gasification temperature and 10 g/min of steam flow rate for 3 kg of initial coal.